O100 The effect of nickel hypersensitivity on outcome of total knee arthroplasty and value of skin patch testing: a systematic review. (22nd July 2022) - Peacock, C; Fu, H; Asopa, V; Clement, N; Kader, D; Sochart, D
Abstract: Introduction Aims: of the systematic review were to assess the sensitising potential of TKA, explore the relationship between Nickel hypersensitivity and clinical outcomes, and evaluate the utility of skin patch testing pre- and/or post-operatively. Methods: A literature search was performed through EMBASE, Medline and PubMed databases. Articles were screened independently by two authors. Levels of Evidence were assessed using OCEBM criteria, and quality assessed using MINORS and Cochrane risk-of-bias tools. Results: Twenty studies met the eligibility criteria, reporting on 1354 knee arthroplasties. Prevalence of Nickel hypersensitivity ranged from 0% to 87.5%. Only one study which compared prevalence of hypersensitivity in the same patient group before and after surgery noted newly positive patch test reactions in 4.1%. Three studies reported lower prevalence of hypersensitivity in post-operative patients compared to pre-operative patients. Seven studies suggested hypersensitivity might cause complications; six studies did not support any relationship. Seven studies recommended pre-operative patch testing in patients with history of metal allergy; nine studies concluded testing may be valuable post-operatively. Conclusion: Patients undergoing TKA do not seem to be at increased risk of developing Nickel hypersensitivity, however there is conflicting evidence that patients with established hypersensitivity are more likely to experience adverse clinical outcomes. Patch testing remains the gold standard diagnostic method; evidence suggests performing this test pre-operatively in patients with history of metal allergy to aid selection of the most appropriate prosthesis, and postoperatively once common causes of implant failure have been excluded, since implant removal or revision with hypoallergenic implants may alleviate symptoms. Take-home message: Patients undergoing total knee arthroplasty do not seem to be at an increased risk of developing nickel hypersensitivity, and there is mixed evidence that patients with hypersensitivity are more likely to experience adverse clinical outcomes. Evidence suggests performing patch testing preoperatively in patients with a history of metal allergy to aid selection of the most appropriate prosthesis, and post-operatively only once more common causes of implant failure have been excluded.